Consumption dispersion between white-collar and blue-collar workers and rising market concentration in the USA: 1984-2011 - Ilhan Dögüs (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2019)
The relationship between consumption inequality (between two groups) and market concentration has hitherto been absent from the literature. This paper argues that consumption dispersion between white-collar and blue-collar workers has caused increased market concentration in the USA in a direct and long-term structural manner. Using data from the Consumption Expenditure Survey (CES) and the St. Louis Fed's FRED datasets, the argument is empirically analyzed based on yearly data for the period 1984-2011 in the USA. The results confirm the existence of a long-term relationship of causality. Applying a vector auto regressive (VAR) model to the data, we find that the variance in market concentration markup due to consumption dispersion starts to rise after the fourth period and reaches 41% in the tenth period.
Keywords: J31; J51; J82; 330; consumption; market concentration; white-collar workers